Concept of Educational Values for Tauhid Nation Education System Perspective - Nur Hadi (Indonesian Journal of Islamic Education Studies (IJIES), 2019)
This study aims to 1) know the values ​​of Tawhid Education in the National Education System. 2) knowing the relevance of the National Education System Law No. 20 of 2003 in strengthening the values ​​of Tawhid Education. This type of research is a literature study literature (library research). The primary source of this research uses Law No. 20 of 2003 concerning the National Education System. The research results obtained 1) Tawhid education values ​​contained in Chapter II Article 3, Chapter V Article 12 paragraph 1 point A, Chapter X Article 36 paragraph 3 point A, and 2) Relevance of the National Education System Law No 20 of 2003 to strengthening the values ​​of Tawheed education that the main purpose is: "Faithful and devoted to the Almighty God". Then the right of the first student is to get religious education in accordance with a religion that is followed and taught by religious educators. And the curriculum is arranged in accordance with the level of education within the framework of the Unitary State of the Republic of Indonesia with the first increase, namely faith and piety.